PENGGUNAAN PIR T-LOOP UNTUK PERBAIKAN I GIGI MOLAR KEDUA PERMANEN RAHANG BAWAH - Shella Indri Novianty (Odonto : Dental Journal, 2017)
Background: Mesial tipping of permanent molar could be corrected by many ways. One of the simplest way was by using T-loop spring. Objective: To report the result of using straight wire appliance system Roth with ¬T-loop spring in order correction of mesial tipping of second lower permanent molar on both side.Case Management: A 35 years old woman came with chief complain wanted to fx the lower left and right molar which was tilted and felt uncomfortable during mastication. OPG examination showed a mesial tipping of 37 and 47 tooth with 300 and 550 angulations. The measurement of angulations was using modifcation of the midline reference plane as used by Elsey and Rock. The straight wire appliance system Roth with .022” slot was used for the treatment. T-loop spring with .018x.022” rectangular stainless steel wire was used to upright of both second permanent molars. Observation of 4 months treatment using T-loop spring showed an improvement in angulations of both second molars; 550 on 37 and 630 on 47.Conclusion: Mesial tipping correction of second permanent molar can beaccomplished using T-loop spring with stainless steel rectangular .018x.022” wire and consistently yields satisfactory result.